Extensive Fetal Congenital Subcutaneous Mixed Venous Lymphatic Lesion: Prenatal Diagnosis and Postnatal Management - I. N. Odibo; L. E. Linam; G. E. Richter; R. J. Jackson; N. K. Dajani (Thieme Medical Publishers, Inc., 2015)
Abstract Vascular lesions may be categorized as proliferative tumors, such as hemangiomas, or nonproliferative malformations that include capillary, lymphatic, venous, arterial, or mixed lesions. Lymphatic malformations are benign localized congenital malformations of the lymphatic system. They may be microcystic or macrocystic lesions or a combination of both. The lesions may also be uniseptate or multiseptate, and are more commonly located in the head and neck or axillary region. Prenatal diagnosis is based on ultrasound and magnetic resonance imaging. Postnatal management largely depends on the size and location of the lesion. This is the first case report of prenatally diagnosed extensive subcutaneous macrocystic venous lymphatic malformation involving the fetal thorax, back, pelvis, and lower extremities. Prenatal course and postnatal management are described. This report will aid other specialists in the field of prenatal diagnosis and postnatal surgery in the evaluation and management of these patients.